2008
DOI: 10.1080/02640410802315419
|View full text |Cite
|
Sign up to set email alerts
|

Playing with confidence: The relationship between imagery use and self-confidence and self-efficacy in youth soccer players

Abstract: Confidence has been one of the most consistent factors in distinguishing the successful from the unsuccessful athletes (Gould, Weiss, & Weinberg, 1981) and Bandura (1997) proposed that imagery is one way to enhance confidence. Therefore, the purpose of the present study was to examine the relationship between imagery use and confidence in soccer (football) players. The participants included 122 male and female soccer athletes ages 11-14 years participating in both house/ recreation (n = 72) and travel/competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 21 publications
3
24
0
5
Order By: Relevance
“…Generally, self-confidence has been positively associated with the growth of adolescents, influencing the development of leadership, self-esteem, and success in sports. 23,31,32 However, this study found that the self-confidence that adolescents feel in cyberspace was associated with negative consequences, such as involvement in cyberbullying. This finding calls for further investigation into the socio-psychological mechanism that mediates cyber-confidence and ''anti-normative behavior'' in social identity theory's terminology 33,34 such as involvement in cyberbullying.…”
Section: Discussionmentioning
confidence: 64%
“…Generally, self-confidence has been positively associated with the growth of adolescents, influencing the development of leadership, self-esteem, and success in sports. 23,31,32 However, this study found that the self-confidence that adolescents feel in cyberspace was associated with negative consequences, such as involvement in cyberbullying. This finding calls for further investigation into the socio-psychological mechanism that mediates cyber-confidence and ''anti-normative behavior'' in social identity theory's terminology 33,34 such as involvement in cyberbullying.…”
Section: Discussionmentioning
confidence: 64%
“…A recent intervention study that focused on the influence of guided imagery and implementation intention on exercise behavior and self-efficacy in the general population supported the potential role of imagery in changes in exercise behavior, although the authors did not find a relation to self-efficacy (Andersson & Moss, 2011). However, the hypothesized relationship between imagery and self-efficacy has been supported in several investigations (Bandura, 1995;Cumming, 2008;Munroe-Chandler, Hall, & Fishburne, 2008;Rodgers, Munroe, & Hall, 2002;Stanley & Cumming, 2007, 2008. A more comprehensive reflection of the relationship of self-efficacy, exercise, and imagery is available in the narrative review by Ross-Stewart et al (2010).…”
Section: Measuring Exercise Imagerymentioning
confidence: 79%
“…First, the players have been exposed to a main psychological technique (i.e. imagery) and taught how to use its various aspects and combinations which could be easily incorporated into daily training programs [27] .…”
Section: Discussionmentioning
confidence: 99%